Perancangan Bengkel Otomasi dan Sistem Ketenagaan di Program Studi Pendidikan Vokasional di Indonesia - Irwanto, Irwanto (Program Studi Magister Manajemen Pendidikan, 2024)
Abstract: Vocational education has the main goal of producing skilled workers, budding entrepreneurs and lifelong learners. So it is highly hoped that electrical engineering vocational education must have adequate workshops and laboratories to train students' skills. They aim to develop individual potential in adopting and adapting to developments in science, technology, art, as well as the demands of qualifications and competencies in the current and future world of work. To achieve this goal, vocational education really needs adequate facilities and infrastructure to support quality learning activities, especially in the electrical engineering vocational education department.Key words: design; workshop; laboratory; vocational education; electrical EngineeringDOI: 10.23960/jmmp .v12.i1.2024.02